Customer loyalty towards Terengganu Equestrian Resort / Mohd Azraf Zakaria - Zakaria, Mohd Azraf (Faculty of Business and Management, 2011)
Customer loyalty is one factor the successful of the organization to achieve competitive advantages in the business. There are five types of factors that contributed customer loyalty which are facilities, location, services offering, physical environment and employees. High motivation among employees, well maintained facilities, good information regarding location and provide quality services can make the customers become loyal to the organization. The aim of this study to investigate the relationship of the independent variables: facilities, location, services offering, physical environment and employees toward customer’s loyalty at Terengganu Equestrian Resort, (TER), Terengganu Darul Iman. Data were collected from 50 respondents and they are randomly selected from customers at TER.